Investigation of ischemia modified albumin, oxidant and antioxidant markers in acute myocardial infarction - Hazini, Ahmet; CEMEK, Mustafa; IŞILDAK, İbrahim; Alpdagtas, Saadet; Onul, Abdullah; Senel, Unal; Kocaman, Tuba; Dur, Ali; Iraz, Mustafa; Uyarel, Huseyin (My University, 2015)
Introduction: Acute myocardial infarction (AMI) is still one of the most common causes of death worldwide. In recent years, for diagnosis of myocardial ischemia, a new parameter, called ischemia modified albumin (IMA), which is thought to be more advantageous than common methods, has been researched.